2020
DOI: 10.1002/etc.4615
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends (1981–2013) of Per‐ and Polyfluoroalkyl Substances and Total Fluorine in Baltic cod (Gadus morhua)

Abstract: Temporal trends from 1981 to 2013 of 28 per-and polyfluoroalkyl substances (PFASs) were investigated in liver tissue of cod (Gadus morhua) sampled near southeast Gotland, in the Baltic Sea. A total of 10 PFASs were detected, with ∑ 28 PFAS geometric mean concentrations ranging from 6.03 to 23.9 ng/g ww. Perfluorooctane sulfonate (PFOS) was the predominant PFAS, which increased at a rate of 3.4% per year. Most long-chain perfluoroalkyl carboxylic acids increased at rates of 3.9 to 7.3% per year except for perfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 86 publications
(111 reference statements)
2
21
0
Order By: Relevance
“…Short-chain polyfluoroalkyl substances were found in high concentration among most water samples, reaching 97%, while long-chain polyfluoroalkyl substances only accounted for 3%. The shortchain PFASs played a crucial part in water samples, in contrast to the different conclusions from previous reports several years ago (Kelly, 2009;Ahrens et al, 2010;Naile et al, 2010;Schultes et al, 2020). It was reported that short-chain PFASs had a high detection level in recent years, which was consistent with these studies (Xu et al, 2014;Wang et al, 2016a;Li et al, 2020a).…”
Section: Concentration and Composition Of Per-and Polyfluoroalkyl Substances In Watersupporting
confidence: 79%
“…Short-chain polyfluoroalkyl substances were found in high concentration among most water samples, reaching 97%, while long-chain polyfluoroalkyl substances only accounted for 3%. The shortchain PFASs played a crucial part in water samples, in contrast to the different conclusions from previous reports several years ago (Kelly, 2009;Ahrens et al, 2010;Naile et al, 2010;Schultes et al, 2020). It was reported that short-chain PFASs had a high detection level in recent years, which was consistent with these studies (Xu et al, 2014;Wang et al, 2016a;Li et al, 2020a).…”
Section: Concentration and Composition Of Per-and Polyfluoroalkyl Substances In Watersupporting
confidence: 79%
“…This indicates that PFAS bioaccumulation in European chub was not sex-dependent for the life stages considered in our study (i.e. mostly immature individuals), as observed elsewhere (Gewurtz et al, 2012;Pan et al, 2014;Arinaitwe et al, 2020;Schultes et al, 2020). Here, fish length influence was not significant, while it was an important driver of PFAS bioaccumulation in the cyprinid Barbus barbus from the Rhône River (Babut et al, 2017) or in the common sole Solea solea from the Gironde estuary (Munoz et al, 2017a).…”
Section: Influence Of Selected Factors On the Bioaccumulation Of Pfassupporting
confidence: 72%
“…In the Arctic, there are sustained or increasing (post‐2010) PFAA levels in some wildlife (Muir et al 2019). Following the phaseout of the parent chemical to PFOS and its precursors circa 2000 to 2002, several studies have noted rapid declines in FOSA, an atmospheric precursor to PFOS that is biotransformed by most mammals, but less consistent declines or even increases in PFOS (Smithwick et al 2006; Ahrens et al 2009a; Dassuncao et al 2017; Sun et al 2019; Schultes et al 2020). This likely reflects the rapid response of atmospheric concentrations to changes in chemical production but a lagged response of most aquatic ecosystems.…”
Section: Current Understanding Of Pfas Exposure In Wildlifementioning
confidence: 99%
“…This likely reflects the rapid response of atmospheric concentrations to changes in chemical production but a lagged response of most aquatic ecosystems. Most time series studies have focused on targeted PFAS, but recent work has shown that trends in total fluorine indicated by EOF and other methods differ from the legacy compounds (Schultes et al 2020). Understanding temporal and spatial trends in emerging PFAS compounds in biota is thus an important research need (Spaan 2020).…”
Section: Pfas Occurrence and Temporal Trends In Wildlifementioning
confidence: 99%